Generic channel overlap calculations algorithm - Oudah, A. (2012)
The ever-increasing shortage of the spectrum leaves fourth generation wireless technologies no choice but to re-use their existing spectra repeatedly by the so-called re-farming strategy. This alternative, nevertheless, increases overlap levels between cells and rapidly escalates into interference situations. In this paper, channel overlap in wireless systems is defined and quantified. The proposed models account for cross and adjacent types of overlap in almost any radio network.